KONSEP KETATANEGARAAN PAKISTAN PERSPEKTIF FIQH SIYASAH - Muhammad Faqih; Ellyda Retpitasari (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2021)
The purpose of this research is to find out the pakistani constitutional system in terms of tate institutions and fiqh siyasah. The method used is library reaserch with two approaches, namely conseptual approach and historical approach. The results of the research of the concept of Pakistani state regulation fiqh siyasah perspective in the era: (1) In general the state of Pakistan can be said to be a country with a weak democracies system, this is motivated by the unstable system of government and constitutional system since Pakistan's independence in 1947. In addition, the cause of the instability of the country is the violence and feud between three social forces, namely Hindus who are the majority in India, indian Muslims who are minorities and The British as invaders with modern political and technological forces that developed in the country of pakistan. (2) The establishment of the Indian Muslim League, Muhammad Ali Jinnah initiated the theory of "two nations" and formally presented the demands of a Muslim homeland separate from India. In a 1940 resolution the Muslim League conveyed the establishment of an independent and fully sovereign Pakistani state. (3) On 15 August 1947 Pakistan was born as a fully sovereign state for Indian Muslims. Islam and Muslims in Pakistan have made a real contribution in the development of civilization in the Islamic world. Pakistan is a country that takes Islam as a source of law has become a phenomenon in the study of the relationship of the country and religion in Islam.